(3CKQ JWHjb GdJMhd GdQbej Ydi EYOGO GdehGRfI GdYGeI ddOhdI hGdQbGHI Ydi JfajPgG HGdhMOGJ GdEOGQjI GdMchejI (B/s - (3,TjQjf Ydi eMeO eMehOs; (3YHO GdYRjR GdSjO eUWais; (3gGfi QLH QRbs (2024)
(3JgOa gPg GdOQGSI Edi bjGS CKQ JWHjb GdJMhd GdQbej Ydi EYOGO GdehGRfI GdYGeI ddOhdI hGdQbGHI Ydi JfajPgG HGdhMOGJ GdEOGQjI GdMchejI, ceG JJfGhd GdeYhbGJ GdJj bO JhGLg GdJMhd GdQbej aj Jdc GdeQGMd(B. (3dJMbjb GdgOa GdSGHb bGeJ GdHGMKI HELQGA OQGSI ejOGfjI Ydi GdhMOGJ GdGOGQjI GdMchejI GdeUQjI, MjK JeKd eLJeY GdOQGSI aj LejY GdhMOGJ GdEOGQjI GdMchejI GdeUQjI, hHdZJ YjfI GdOQGSI (B165 (3eaQOI, hbO Je JMdjd GdHjGfGJ hGNJHGQ aQhV GdOQGSI HGSJNOGe GdCSGdjH GdEMUGFjI GdhUajI heYGed GQJHGW HjQShf hMReI GdHQGeL GdEMUGFjI ddYdhe GdGLJeGYjI (BSPSS 27.(3JhUdJ fJGFL GdJMdjd GdEMUGFi ddOQGSI Edi hLhO JCKjQ GjLGHi eYfhi ddJMhd GdQbej Ydi EYOGO hJfajP GdehGRfI, hcPdc hLhO JCKjQ GjLGHi heYfhi ddJMhd GdQbej Ydi GdQbGHI Ydi JfajP GdehGRfI , HGdEVGaI Edi YOe hLhO aQhb eYfhjI Hjf YjfI GdOQGSI HTCf eYhbGJ GdJMhd GdQbej hJCKjQg Ydi eQMdI GdEYOGO hGdJfajP hGdQbGHI Ydi GdehGRfI GdYGeI ddOhdI GdeUQjI JQLY ai GdYhGed GdOjehZQGajI(B.s
This study aims to measure the impact of implementing digital transformation on the preparation of the state$1 (Bs general budget and the controlling of its execution in government administrative units. It also addresses the obstacles that may hinder digital transformation during these phases. To achieve the aforementioned objective, the researcher conducted a field study on Egyptian government administrative units. The study population consisted of all Egyptian government administrative units, with a sample size of 165 units. Data were analyzed, and the study's hypotheses were tested using descriptive statistical methods, Pearson correlation coefficient, and the Statistical Package for the Social Sciences (SPSS 27). The statistical analysis results revealed a significant positive impact of digital transformation on both the preparation and execution of the budget. Additionally, there was a significant positive impact of digital transformation on controlling budget execution. Furthermore, the study found no significant differences among the sample regarding the obstacles to digital transformation and its effect on the preparation, execution, and controlling phases of the Egyptian state$1 (Bs general budget, attributable to demographic factorss
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024.s
(3HHdjhLQGajG(B: (3UaMGJ (B155-175.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdejRGfjIs -- (3eMGSHIs; (3GdejRGfjIs -- (3GdQbGHIs; (3GdJMhd GdQbejs -- (3EYOGO GdehGRfI GdYGeI ddOhdIs -- (3GdQbGHI Ydi JfajP GdehGRfI GdYGeI ddOhdIs